Blackwater Fever in Ugandan Children With Severe Anemia is Associated With Poor Postdischarge Outcomes: A Prospective Cohort Study. (12th July 2019) - Opoka, Robert O; Waiswa, Ali; Harriet, Nambuya; John, Chandy C; Tumwine, James K; Karamagi, Charles
Abstract: Background: Blackwater fever (BWF), one of the complications of severe malaria, has recently re-emerged as a cause of severe anemia (SA) in African children. However, postdischarge morbidity in children with BWF has previously not been described. Methods: This was a descriptive cohort study in which children, aged 0–5 years, admitted to Jinja Regional Referral Hospital with acute episodes of SA (hemoglobin ≤5.0 g/dL) were followed up for 6 months after hospitalization. Incidence of readmissions or deaths during the follow-up period was compared between SA children with BWF and those without BWF. Results: A total of 279 children with SA including those with BWF (n = 92) and no BWF (n = 187) were followed for the duration of the study. Overall, 128 (45.9%) of the study participants were readmitted at least once while 22 (7.9%) died during the follow-up period. After adjusting for age, sex, nutritional status, and parasitemia, SA children with BWF had higher risk of readmissions (hazard ratio [HR], 1.68; 95% confidence interval [CI], 1.1–2.5) and a greater risk of death (HR. 3.37; 95% CI, 1.3–8.5) compared with those without BWF. Malaria and recurrence of SA were the most common reasons for readmissions. Conclusions: There is a high rate of readmissions and deaths in the immediate 6 months after initial hospitalization among SA children in the Jinja hospital. SA children with BWF had increased risk of readmissions and deaths in the postdischarge period. Postdischarge malaria chemoprophylaxis should be considered for SA children living in malaria endemic areas. Abstract : There is a high frequency of postdischarge readmissions and deaths in children with severe anemia, especially in severe anemia associated with blackwater fever. Postdischarge malaria prophylaxis should be considered in children with severe anemia.